Influences of Problem-Based Learning Models on Class XI Students Learning Outcomes in Subject of Light Vehicle Engine Maintenance at KAL-1 Vocational School Surabaya - Wahyuni, Dian; Samani, Muchlas; Wiyanto, Theodorus; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
The study aims to determine student learning outcomes with direct and problem-based learning models,to determine differences in student outcomes with intelligence levels in direct and problem-based learning models, and analyze the relationship between intelligence levels and direct learning models and problem-based learning models. The method  used in this study was experimentation using factorial research design. The design used is 2x2 factorial design, as this design can be used to see students ' learning outcomes before they are given learning and after learning. The results of the study found that: (1) Student learning outcomes using PBL  models are significantly higher than those using MPL;(2) student learning outcomes who have higher mathematic logic intelligence using  PBL  models  are significantly higher than students who are taught with MPL models;(3)student learning outcomes who have lower mathematic logic intelligence using MPL models are significantly higher than students who are taught with PBL models;(4) There is a significant interaction between the level of intelligence of mathematical logic, learning models in student learning outcomes. The study concluded that:  (1)  The  PBL  learning  model  can  increase  the  student learning outcomes than MPL models;  (2)  Students  who  have  a  higer mathematic logic intelligence using PBL models, higher learning outcomes than student with MPL models;(3) student who have a lower mathematic logic intelligence using MPL models, higher learning outcomes than student with PBL model, and (4) there is an interaction between the level of intelligence of mathematical logic, learning models in student learning outcomes